History, innovation and establishment of Islamic culture course in the Arabic Universities: Qatar experience as an example (Islamic Sciences Journal, 2023)
This research sheds light on the early beginnings of the inception of Islamic Culture course by Sheikh Muhammed Ragheb   Al-Tabbakh, who wrote a book for students of Sharia institutes in Aleppo and Damascus. Ragheb Al-Tabbakh’s book differs in content from the book written by Muhammed   Al-Mubarak’s book (the Scheme of Islam), which was then termed as “Islamic Culture”. The book presents Islam as a ‘comprehensive scheme’. This study focuses on the role of Muhammed   Al-Mubarak in making his book acknowledge and approved by the Association of Arab Universities. The study also demonstrates Muhammed Al-Mubarak’s role in significantly contributing in preparing ‘Islamic syllabuses’ in different Arab Universities. The study then addresses Adnan Zarzour enormous contributions to Islamic culture and university syllabuses. In the last section, the study talks about Muhammed Al-Musleh who is considered as one of the most well-known students of Adnan Zarzour at Qatar University. Qatar University has adopted a creative development strategy to re-examine and improve the prescribed syllabus at both theoretical and practical levels. There is a need to develop the syllabus, especially as a result of recent challenges that the modern generation encountered with.